2014
DOI: 10.1590/0074-0276140046
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory viruses by real-time polymerase chain reaction in outpatients with acute respiratory infection

Abstract: Viruses are the major contributors to the morbidity and mortality of upper and lower acute respiratory infections (ARIs) for all age groups. The aim of this study was to determine the frequencies for a large range of respiratory viruses using a sensitive molecular detection technique in specimens from outpatients of all ages with ARIs. Nasopharyngeal aspirates were obtained from 162 individuals between August 2007-August 2009. Twenty-three pathogenic respiratory agents, 18 respiratory viruses and five bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
5
12
1
1
Order By: Relevance
“…This was in contradiction with some older studies, which reported around 2%-10% atypical bacteria in ILI/ARI patients [16][17][18]. We also expected to detect more cases with especially atypical bacteria in our study but realized that our results were in agreement with a recent study of outpatients presenting with ILI/ARI where the investigators similarly could not detect any bacterial etiology [19]. We suggest that our results represent the true etiology of ILI/ARI in our region, as otherwise we could detect more than one case, given our sampling distribution over five months.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was in contradiction with some older studies, which reported around 2%-10% atypical bacteria in ILI/ARI patients [16][17][18]. We also expected to detect more cases with especially atypical bacteria in our study but realized that our results were in agreement with a recent study of outpatients presenting with ILI/ARI where the investigators similarly could not detect any bacterial etiology [19]. We suggest that our results represent the true etiology of ILI/ARI in our region, as otherwise we could detect more than one case, given our sampling distribution over five months.…”
Section: Discussioncontrasting
confidence: 99%
“…We suggest that this difference was due to the age characteristics of the study populations, which included infants and children ≥ 6 months of age in Zimmerman et al's study. Similarly, the predominant viruses in the study from Brazil mentioned above [19], influenza and rhinovirus, were not as prevalent as in our study. This difference may be due to the non-temperate climate in our region, as higher activity of influenza virus can be encountered in regions with a humid climate [21].…”
Section: Discussionsupporting
confidence: 47%
“…Pneumonia is the major clinical presentation of lower acute respiratory tract infection, which is considered as the major cause of hospitalization among children worldwide. e mortality and morbidity rate is higher especially during the first years of life [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence was assessed at the amplification step. The positive and negative virus plasmid controls provided in the kit were included in all runs to monitor assay performance …”
Section: Methodsmentioning
confidence: 99%